Uniwerbizacja wyrażeń rzeczownik + przymiotnik we współczesnych rosyjskich i czeskich czasopismach ekonomicznych (aspekt porównawczy) - Mrověcová, Ljuba (Przegląd Rusycystyczny, 2006)
UNIWERBIZACJA WYRAŻEŃ RZECZOWNIK + PRZYMIOTNIK WE WSPÓŁCZESNYCH ROSYJSKICH I CZESKICH CZASOPISMACH EKONOMICZNYCH (ASPEKT PORÓWNAWCZY) Streszczenie W artykule zanalizowano i porównano wyrażenia rzeczownik + przymiotnik we współczesnej rosyjskiej i czeskiej prasie ekonomicznej.Przedstawiono analizę strukturalno-semantyczną, leksykalno-semantyczną oraz etymologiczną zebranego materiału językowego. UNIVERBISAtION OF NOUN-ADJECTIVE COLLOCATIONS IN CONTEMPORARY RUSSIAN AND CZECH BUSINESS MAGAZINES — COMPARATIVE APPROACH Summary In the article, the author analyses one of the types of Russian compounds, which are used in present Russian texts related to business, in comparison on with Czech. the first part of the paper is aimed at categorizing analytic adjectives and compounds, which are the result of the processes of abbreviating and composing. In the second part it is suggested that another category should be introduced due to the overlapping of the mentioned processes.